KOH modified activated carbon supported copper catalyst for low-temperature NH3-SCR denitration as well as preparation method and application of KOH modified activated carbon supported copper catalyst

Through the KOH modified activated carbon load copper catalyst, the problem of limited active activity sites of activated carbon catalysts is solved, and high -efficiency nitrogen oxide denitration under low temperature conditions is achieved, which significantly improves the denitration rate.

CN119368187APending Publication Date: 2025-01-28WUHAN UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411208097.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the activated carbon catalyst has limited active sites, resulting in poor denitrification rate of nitrogen oxides in coke oven flue gas under low temperature conditions.

Method used

By using the KOH modified activated carbon load copper catalyst, the specific steps include crushing and grinding coal-based activated carbon, add KOH for activation treatment, and load copper salt through impregnation reactions to form an AC-XK-YCU catalyst.

Benefits of technology

The pore structure and activity sites of the catalyst have been improved, and high -efficiency denitration below 200 ° C is achieved, which significantly improves the removal rate of nitrogen oxides in the furnace flue gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368187A_ABST
    Figure CN119368187A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of activated carbon and coke oven flue gas denitration, and discloses a KOH modified activated carbon supported copper catalyst for low-temperature NH3-SCR denitration as well as a preparation method and application of the KOH modified activated carbon supported copper catalyst. The preparation method of the KOH modified activated carbon supported copper catalyst specifically comprises the following steps: weighing coal-based activated carbon, crushing, grinding and screening to obtain activated carbon particles, carrying out suction filtration, washing and drying on the activated carbon particles, uniformly mixing with KOH to obtain a mixed material, carrying out an activation reaction on the mixed material to obtain activated activated carbon, and drying to obtain the KOH modified activated carbon supported copper catalyst. And washing the activated active carbon until the filtrate is neutral, drying, grinding and screening to obtain an active carbon carrier, carrying out equivalent-volume impregnation reaction on the active carbon carrier and a copper salt solution, and drying to obtain the KOH modified active carbon supported copper catalyst. The KOH modified activated carbon supported copper catalyst can be used for treating nitrogen oxides in coke oven flue gas at the temperature of 100-220 DEG C, active sites are increased, and the catalytic effect of denitration reaction is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of activated carbon and coke oven flue gas denitration, and in particular to a KOH-modified activated carbon-loaded copper catalyst for low-temperature NH3-SCR denitration, and a preparation method and application thereof. Background Art

[0002] Due to the increase in air pollutant emissions from traditional fossil fuels such as coal and oil, it is urgent to control nitrogen oxide emissions. X ) is the general term for NO, NO2, N2O, and N2O5. This type of pollutant can quickly destroy the ozone layer and bring about photochemical smog, acid rain and other severe weather conditions, which is the key factor in the formation of smog weather. In addition, NO X It can enter the human body through the respiratory or skin system, dissolve and accumulate in the alveolar fluid, and partially convert into nitrate or nitrite species to corrode lung tissue; nitrite species can also spread to the blood system, combine with hemoglobin to form methemoglobin, causing the human body to lack oxygen and suffocate. Therefore, it is very necessary to study the removal of nitrogen oxides in coke oven flue gas.

[0003] NO X The production of NO can be divided into natural and artificial production. X Usually produced by lightning, soil microorganisms, etc. Most of the anthropogenic ones come from the burning of fossil fuels for power generation, transportation and other incineration processes. X Emission reduction methods can be divided into pre-combustion treatment, combustion control and post-combustion treatment. Pre-combustion treatment and combustion control can only achieve NO X The most commonly used technologies for the removal of low NOx emissions are selective non-catalytic reduction (SNCR) and selective catalytic reduction (SCR). SNCR has a high operating temperature but low denitrification efficiency and is suitable for power plants with lower emissions. The selective catalytic reduction (SCR) denitrification technology using NH3 as a reductant is currently the most popular technology for removing NOx from flue gas. X The mainstream technology of denitration is the SCR denitration technology. However, the mature denitration catalyst developed by thermal power plants cannot be further promoted and applied in non-electric low-temperature (<250℃) fields (sintering, pelletizing, kilns, etc.) due to its narrow temperature window (300-400℃). Therefore, the development of low-temperature SCR denitration catalysts that can work below 200℃ has important practical significance and application value.

[0004] Generally speaking, the core of NH3-SCR technology lies in the catalyst, and activated carbon, as a commonly used NH3-SCR catalyst or catalyst carrier in industry, has a need to improve its denitrification capacity and a relatively low air velocity. In the NH3-SCR reaction, the denitrification rate is related to the structure and active components of the catalyst. When the effective pore size of the activated carbon is 1.7-3 times the molecular diameter of the adsorbate, it is conducive to adsorption. Micropores provide active sites for adsorption and are the main site of adsorption. Mesopores increase the diffusion rate of the reaction and reduce the diffusion resistance. Diversified pore sizes can further improve the adsorption capacity, but the active sites of coal-based activated carbon are limited. The effect of selecting metal modification is relatively superior, and copper can receive electron pairs as Lewis acid sites, which is conducive to the adsorption of NH3. Therefore, it is necessary to enrich the pore size types, increase the specific surface area and increase the active sites on the basis of the activated carbon carrier. Summary of the invention

[0005] Based on the above, the purpose of the present invention is to provide a KOH-modified activated carbon-loaded copper catalyst for low-temperature NH3-SCR denitrification and its preparation method and application, so as to solve the problem that the active sites of the activated carbon catalyst are limited and the denitrification rate within the flue gas temperature window is poor.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] An activated carbon carrier for low-temperature NH3-SCR denitration, the general formula of the activated carbon carrier is: AC-xK;

[0008] Wherein, AC is coal-based activated carbon, K is the activator KOH, x is the mass ratio of KOH to AC, and x is 1-6.

[0009] A method for preparing an activated carbon carrier for low-temperature NH3-SCR denitration comprises the following steps:

[0010] Weigh coal-based activated carbon, crush it, grind and sieve it to obtain activated carbon particles;

[0011] The activated carbon particles are filtered, washed, dried, and then mixed evenly with KOH to obtain a mixed material;

[0012] The mixed material is subjected to an activation reaction under the protection of an inert atmosphere to obtain activated activated carbon;

[0013] The activated carbon is washed until the filtrate is neutral, dried, ground and sieved to obtain an activated carbon carrier.

[0014] As a preferred embodiment of the method for preparing an activated carbon carrier for low-temperature NH3-SCR denitrification, the mass ratio of the activated carbon particles to the KOH is 1:(1-6).

[0015] As a preferred embodiment of the method for preparing an activated carbon carrier for low-temperature NH3-SCR denitrification, during the activation reaction, the mixed material is heated from room temperature to 600-900°C at 5°C / min under the protection of an inert atmosphere and kept warm for 1-2h.

[0016] As a preferred embodiment of the method for preparing an activated carbon carrier for low-temperature NH3-SCR denitrification, the particle size of the activated carbon particles is 20-60 meshes, and the particle size of the activated carbon carrier is 40-60 meshes.

[0017] A KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitration, wherein the KOH-modified activated carbon-supported copper catalyst has a general formula of: AC-xK-yCu;

[0018] Wherein, AC is coal-based activated carbon, K is activator KOH, x is the mass ratio of KOH to AC, x is 1-6, and y is the loading amount of Cu, y is 1wt%-15wt%.

[0019] A method for preparing a KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitration, based on any one of the above-mentioned activated carbon carriers for low-temperature NH3-SCR denitration, comprises the following steps:

[0020] The activated carbon carrier is impregnated with equal volumes of nitrate solution for reaction, and then dried to obtain a KOH-modified activated carbon-supported copper catalyst.

[0021] As a preferred scheme for the preparation of a KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitrification, the copper salt solution includes a mixture of Cu(NO3)2·3H2O and deionized water; in the KOH-modified activated carbon-supported copper catalyst, the loading amount of Cu is 1wt%-15wt%.

[0022] Application of a KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitration, wherein the KOH-modified activated carbon-supported copper catalyst is used for denitration reaction to remove NO in coke oven flue gas X .

[0023] As a preferred scheme for the application of KOH-modified activated carbon-loaded copper catalyst for low-temperature NH3-SCR denitrification, the denitrification reaction specifically includes the following steps: placing the KOH-modified activated carbon-loaded copper catalyst in a quartz tube, filling both ends of the quartz tube with quartz sand and quartz wool, and then placing the quartz tube in a reaction device, and introducing a mixed gas of NH3, NO, O2 and N2; wherein the total flow rate of the mixed gas is 100ml / min-300ml / min, and the reaction temperature is 100℃-220℃.

[0024] The beneficial effects of the present invention are:

[0025] The present invention provides a KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitration and its preparation method and application. KOH-activated activated carbon and an equal volume of impregnated modified activated carbon are used as NH3-SCR catalysts. Cu is used as a low-temperature active site and the excellent pore structure of KOH-activated activated carbon is used to improve the catalytic effect and achieve a higher denitration rate under the dual advantages. In addition, the method can effectively treat nitrogen oxides (NO X ), the reaction conditions are mild, which reduces energy loss and resource waste. At the same time, the catalytic operation is simple, the reaction is easy to control, and the feasibility is strong. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.

[0027] Figure 1 It is a comparison chart of the denitration performance of AC-xK prepared by the present invention in the denitration reaction;

[0028] Figure 2 is a nitrogen adsorption-desorption curve diagram of AC-xK prepared by the present invention;

[0029] Figure 3 is the pore size distribution diagram of AC-xK prepared by the present invention;

[0030] Figure 4 It is a comparison chart of the denitration performance of the AC-4K-yCu catalysts with different Cu loadings prepared by the present invention in the denitration reaction. DETAILED DESCRIPTION

[0031] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.

[0032] This embodiment provides a KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitration, and the specific preparation method includes:

[0033] S100: weighing coal-based activated carbon, crushing it, grinding and screening it to obtain activated carbon particles;

[0034] Specifically, the particle size of the activated carbon particles is 20-60 mesh.

[0035] Preferably, the carrier used in the present invention is coal-based activated carbon. In practical industrial applications, the carrier includes but is not limited to coal-based activated carbon. It has excellent specific surface area, porous structure and rich functional groups. The active ingredients can be well dispersed and form a monolayer covering on the carbon material. It is an ideal catalyst or carrier in heterogeneous catalysis.

[0036] S200: filtering, washing, drying and evenly mixing the activated carbon particles with KOH to obtain a mixed material;

[0037] Specifically, the mass ratio of activated carbon particles to KOH is 1:(1-6), and the mass ratio can be 1:1 or 1:2 or 1:4 or 1:6, which is determined according to actual conditions. Adding KOH alkali treatment can expand the pore size of activated carbon, increase the specific surface area of ​​activated carbon, and improve denitrification performance.

[0038] Specifically, the mixture is filtered and washed 6-8 times to remove ash, and dried in an oven at 100° C. for 12-24 hours.

[0039] S300: performing an activation reaction on the mixed material under the protection of an inert atmosphere to obtain activated activated carbon;

[0040] Specifically, during the activation reaction, the mixed material is heated from room temperature to 600-900°C at 5°C / min under the protection of an inert atmosphere, and kept warm for 1-2 hours. The activation temperature may be 600°C, 800°C or 900°C, which is determined according to actual conditions. The inert atmosphere includes a nitrogen atmosphere.

[0041] S400: washing the activated carbon until the filtrate is neutral, drying, grinding and screening to obtain an activated carbon carrier;

[0042] Specifically, the activated product is washed with weak acid for several times until the filtrate is neutral and then transferred to a 100° C. oven for drying for 12-24 hours; the particle size of the activated carbon carrier is 40-60 meshes.

[0043] More specifically, the general formula of the activated carbon carrier is: AC-xK, wherein AC is coal-based activated carbon, K is the activator KOH, x is the mass ratio of KOH to AC, and x is 1 to 6. x can be 1 or 2 or 4 or 6, which is determined according to the actual situation.

[0044] S500: The activated carbon carrier is impregnated with equal volumes of nitrate solution for reaction, and then dried to obtain a KOH-modified activated carbon-supported copper catalyst.

[0045] Specifically, during the equal volume impregnation reaction, the activated carbon carrier is first weighed to measure the water absorption rate, and the required amount of nitrate is calculated based on the result of the water absorption rate, and the nitrate is dissolved in deionized water, and the mixture is fully mixed by ultrasonic vibration for 10-120s to prepare a nitrate solution, and the nitrate solution is added dropwise to the activated carbon carrier, and the mixture is allowed to stand for 7 hours, and then the sample is dried at 100°C for 12-24 hours to remove moisture. In the prepared KOH-modified activated carbon-supported copper catalyst, the loading amount of Cu is 1wt%-15wt%.

[0046] More specifically, the general formula of KOH-modified activated carbon-supported copper catalyst is: AC-xK-yCu; wherein AC is coal-based activated carbon, K is activator KOH, x is the mass ratio of KOH to AC, x is 1-6, y is the loading amount of Cu, y is 1wt%-15wt%. x can be 1, 2, 4, 6, and y can be 1wt%, 3wt%, 5wt%, 10wt%, 15wt%, which is determined according to actual conditions.

[0047] The present invention will be further described below by means of specific examples.

[0048] Example 1

[0049] Take a certain amount of coal-based activated carbon, crush it to 20-60 meshes with a pulverizer, filter it, wash it 6-8 times to remove the ash, transfer it to a 100°C oven to dry for 12 hours, and then store it in a dryer for later use. Take 3g of the crushed and dried activated carbon and 3g of KOH and mechanically mix them in a nickel ark. The mixed sample is transferred to a tubular furnace in a nitrogen atmosphere, where the mass ratio of KOH to activated carbon is 1:1, the flow rate of N2 is 80mL / min, the activation temperature is 800°C, and the temperature is kept for 120 minutes. After activation, the activated material is filtered and washed several times with weak acid until the filtrate is neutral, and then dried in a 100°C oven for 20 hours to obtain a catalyst activated carbon carrier, which is represented by AC-1K.

[0050] Example 2

[0051] Take a certain amount of coal-based activated carbon, crush it to 20-60 meshes with a pulverizer, filter and wash it 6-8 times to remove ash, transfer it to a 100°C oven to dry for 16 hours, and then store it in a dryer for later use. Take 3g of the crushed and dried active particles and 6g of KOH in a nickel ark for mechanical mixing, and transfer the mixed sample to a tubular furnace in a nitrogen atmosphere, where the mass ratio of KOH to activated carbon is 2:1, the flow rate of N2 is 80mL / min, the activation temperature is 800°C, and the temperature is kept for 90 minutes. After activation, the activated material is filtered and washed several times with weak acid until the filtrate is neutral, and then dried in a 100°C oven for 16 hours to obtain a catalyst activated carbon carrier, which is represented by AC-2K.

[0052] Example 3

[0053] Take a certain amount of coal-based activated carbon, crush it to 20-60 meshes with a pulverizer, filter it, wash it 6-8 times to remove the ash, transfer it to a 100°C oven to dry it for 20 hours, and then store it in a dryer for later use. Take 3g of the crushed and dried activated carbon and 12g of KOH and mechanically mix them in a nickel ark. The mixed sample is transferred to a tubular furnace in a nitrogen atmosphere, where the mass ratio of KOH to activated carbon is 4:1, the flow rate of N2 is 80mL / min, the activation temperature is 800°C, and the temperature is kept for 90 minutes. After activation, the activated material is filtered and washed several times with weak acid until the filtrate is neutral, and then dried in a 100°C oven for 12 hours to obtain a catalyst activated carbon carrier, which is represented by AC-4K.

[0054] Example 4

[0055] Take a certain amount of coal-based activated carbon, crush it to 20-60 meshes with a pulverizer, filter it, wash it 6-8 times to remove the ash, transfer it to a 100°C oven to dry it for 24 hours, and then store it in a dryer for later use. Take 3g of the crushed and dried activated carbon and 18g of KOH and mechanically mix them in a nickel ark. The mixed sample is transferred to a tubular furnace in a nitrogen atmosphere, where the mass ratio of KOH to activated carbon is 6:1, the flow rate of N2 is 80mL / min, the activation temperature is 800°C, and the temperature is kept for 60 minutes. After activation, the activated material is filtered and washed several times with weak acid until the filtrate is neutral, and then dried in a 100°C oven for 24 hours to obtain a catalyst activated carbon carrier, which is represented by AC-6K.

[0056] The alkali-treated catalyst activated carbon carrier AC-xK prepared in Examples 1, 2, 3, and 4 was subjected to a denitrification reaction. The catalyst was evaluated using a multi-gas fixed bed reactor, and NH3, NO, O2, and N2 were introduced. The total flow rate of the mixed gas was 300 ml / min, and NO X The concentration is 500ppm, the NH3 concentration is 600ppm, the O2 is 5.5% Vol., and the reaction temperature is 100℃-220℃. The granulated catalyst is placed in a quartz tube with an inner diameter of 7mm, and loaded into a fixed bed reactor, and filled with quartz sand and quartz wool. The catalyst is loaded with about 0.4g, 40-60 mesh, and the air velocity is 12000h -1 , and evaluate the denitrification performance.

[0057] The performance results are as follows Figure 1 As shown, Figure 1The performance comparison diagram of AC-xK prepared by the present invention in the denitration reaction is shown. By comparing the denitration efficiency at different temperatures, the performance differences of various catalysts in the temperature range of 100-220°C are observed. The AC-xK prepared by the present invention all have good catalytic effects, among which AC-4K prepared in Example 3 has the best catalytic performance. In the entire temperature window of 100-220°C, the denitration efficiency of AC-4K is always maintained at a high level.

[0058] The alkali-treated catalyst activated carbon carrier AC-xK prepared in Examples 1, 2, 3, and 4 was subjected to relevant performance tests. The test results are as follows: Figure 2 , Figure 3 And as shown in Table 1.

[0059] Table 1 Specific surface area, pore diameter, and total pore volume parameters of AC-xK

[0060]

[0061] Table 1 shows the specific surface area, pore size, and total pore volume data of the AC-xK prepared by the present invention using the BET model and the BJH calculation method. As shown in Table 1, as the mass of KOH increases, its specific surface area and total pore volume also increase. Among them, AC-6K has the largest specific surface area, which is 2200.2 m 2 / g. But by Figure 1 It can be seen that its NH3-SCR activity is the worst, which shows that specific surface area is not the only factor affecting NH3-SCR activity. The catalytic ability of the catalyst does not only depend on its surface area, porosity and pore size. Therefore, in order to reduce the amount of KOH and avoid the waste of resources during the filtration and washing process, the optimal NO X Based on conversion rate and higher specific surface area, the present invention uses AC-4K as the metal-modified carrier.

[0062] Figure 2 This is the nitrogen adsorption-desorption curve of AC-xK prepared by the present invention. It can be seen from the figure that the adsorption amount of all materials increases rapidly at a lower relative pressure, the curve is concave, an adsorption hysteresis loop appears in the middle section, and the latter section of the curve is convex again, showing a typical IV type N2 isothermal adsorption-desorption curve.

[0063] Figure 3 The pore size distribution diagram of AC-xK prepared by the present invention, specifically the pore structure characteristics of AC-xK. As can be seen from the figure, the pore sizes of these four catalysts are mainly distributed in the range of 1-10nm, which are micro-mesoporous materials, and all show a relatively concentrated distribution trend, indicating that the pore structure of these materials has good uniformity. It is a relatively ideal carrier that can be used for modification.

[0064] To further illustrate the key point of this patent, the AC-4K prepared above is further reacted. Weigh 1-2g of 40-60 mesh activated carbon carrier to measure water absorption. The test method is: weigh 1-2g of dried AC-4K and 10ml of deionized water, and add deionized water drop by drop into the carrier AC-4K until AC-4K absorbs water to saturation. The volume difference before and after deionized water is the saturated water absorption of AC-4K. The above test can obtain the water absorption rate of AC-4K as 4ml H2O / gAC-4K.

[0065] Example 5

[0066] The catalyst AC-4K prepared in Example 3 was used as an impregnation modified activated carbon carrier, and the transition metal Cu was loaded on it, wherein the loading amount of Cu was 1wt%. According to the measured water absorption rate of AC-4K (40-60 mesh), it was 4ml H2O / gAC-4K. 4ml of deionized water was weighed with a pipette, and 0.038g of Cu(NO3)2·3H2O and deionized water were prepared into a solution, which was placed in an ultrasonic cleaner for 30s to shake and mix evenly, and then added dropwise to the carrier. Then it was allowed to stand for 7h, and dried in a 100°C blast drying oven for 12h to prepare a KOH modified activated carbon supported copper catalyst, which was denoted as AC-4K-1Cu.

[0067] Example 6

[0068] The catalyst AC-4K prepared in Example 3 was used as an impregnation modified activated carbon carrier, and the transition metal Cu was loaded on it, wherein the loading amount of Cu was 3wt%. According to the measured water absorption rate of AC-4K (40-60 mesh), it was 4ml H2O / gAC-4K. 4ml of deionized water was weighed with a pipette, and 0.114g of Cu(NO3)2·3H2O and deionized water were prepared into a solution, which was placed in an ultrasonic cleaner for 30s to shake and mix evenly, and then added dropwise to the carrier. Then it was allowed to stand for 7h, and dried in a 100°C blast drying oven for 16h to prepare a KOH modified activated carbon supported copper catalyst, which was denoted as AC-4K-3Cu.

[0069] Example 7

[0070] The catalyst AC-4K prepared in Example 3 was used as an impregnation modified activated carbon carrier, and the transition metal Cu was loaded on it, wherein the loading amount of Cu was 5wt%. According to the measured water absorption rate of AC-4K (40-60 mesh), it was 4ml H2O / gAC-4K. 4ml of deionized water was weighed with a pipette, and 0.19g of Cu(NO3)2·3H2O and deionized water were prepared into a solution, which was placed in an ultrasonic cleaner for 30s of shaking and mixing, and then added dropwise to the carrier. Then it was allowed to stand for 7h, and dried in a blast drying oven at 100°C for 20h to prepare a KOH modified activated carbon supported copper catalyst, which was denoted as AC-4K-5Cu.

[0071] Example 8

[0072] The catalyst AC-4K prepared in Example 3 was used as an impregnation-modified activated carbon carrier, and the transition metal Cu was loaded on it, wherein the loading amount of Cu was 10wt%. According to the measured water absorption rate of AC-4K (40-60 mesh), it was 4ml H2O / gAC-4K. 4ml of deionized water was weighed with a pipette, and 0.3801g of Cu(NO3)2·3H2O and deionized water were prepared into a solution, which was placed in an ultrasonic cleaner and vibrated for 30s to mix evenly, and then added dropwise to the carrier. Then it was allowed to stand for 7h, and dried in a blast drying oven at 100°C for 24h to prepare a KOH-modified activated carbon-supported copper catalyst, which was denoted as AC-4K-10Cu.

[0073] Example 9

[0074] The catalyst AC-4K prepared in Example 3 was used as an impregnation modified activated carbon carrier, and the transition metal Cu was loaded on it, wherein the loading amount of Cu was 15wt%. According to the measured water absorption rate of AC-4K (40-60 mesh), it was 4ml H2O / gAC-4K. 4ml of deionized water was weighed with a pipette, and 0.5701g of Cu(NO3)2·3H2O and deionized water were prepared into a solution, which was placed in an ultrasonic cleaner for 30s to shake and mix evenly, and then added dropwise to the carrier. Then it was allowed to stand for 7h, and dried in a blast drying oven at 100°C for 12h to prepare a KOH modified activated carbon supported copper catalyst, which was denoted as AC-4K-15Cu.

[0075] The KOH-modified activated carbon-supported copper catalyst prepared in Examples 5-9 was subjected to denitration reaction to test its denitration performance. The denitration performance of the catalyst was evaluated using a multi-gas fixed bed reaction apparatus, with NH3, NO, O2 and N2 introduced, wherein the total flow rate of the mixed gas was 300 ml / min, NO XThe concentration is 500ppm, the NH3 concentration is 600ppm, the O2 is 5.5% Vol., and the reaction temperature is 100℃-220℃. The granulated catalyst is placed in a quartz tube with an inner diameter of 7mm, and loaded into a fixed bed reactor, and filled with quartz sand and quartz wool. The catalyst is loaded with about 0.4g, 40-60 mesh, and the air velocity is 12000h -1 , and evaluate the denitrification performance.

[0076] Figure 4 This is the denitrification performance evaluation diagram of AC-4K-yCu with different Cu loadings. From this figure, we can see that the Cu content has a significant effect on NO X The conversion rate is significantly affected. Within 100-180℃, NO X The order of conversion rate from high to low is AC-4K-10Cu>AC-4K-15Cu>AC-4K-5Cu>AC-4K-3Cu>

[0077] AC-4K-1Cu. The reason may be that when the Cu content is low, it cannot provide enough active centers for the reaction, and when the Cu content is too high, the specific surface area of ​​the catalyst will be reduced, and part of the pore size will be blocked, thereby increasing the diffusion resistance in the pores during the gas-solid reaction, or too much Cu loaded on the surface of AC-4K is prone to form clusters, which reduces the effective active sites and inhibits the activity of the modified AC-4K-yCu catalyst. In the flue gas temperature range of 200-220°C, the denitration rates of the KOH-modified activated carbon-loaded copper catalysts prepared in the above five embodiments all reached more than 89%, among which the denitration rate of AC-4K-5Cu was as high as 99%.

[0078] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.

Claims

1. An activated carbon carrier for low-temperature NH3-SCR denitrification, characterized in that: The general formula of the activated carbon carrier is: AC-xK; Wherein, AC is coal-based activated carbon, K is the activator KOH, x is the mass ratio of KOH to AC, and x is 1-6.

2. The method for preparing an activated carbon carrier for low-temperature NH3-SCR denitrification according to claim 1, characterized in that: The following steps are involved: Weigh coal-based activated carbon, crush it, grind and sieve it to obtain activated carbon particles; The activated carbon particles are filtered, washed, dried, and then mixed evenly with KOH to obtain a mixed material; The mixed material is subjected to an activation reaction under the protection of an inert atmosphere to obtain activated activated carbon; The activated carbon is washed until the filtrate is neutral, dried, ground and sieved to obtain an activated carbon carrier.

3. The method for preparing an activated carbon carrier for low-temperature NH3-SCR denitrification according to claim 2, characterized in that: The mass ratio of the activated carbon particles to the KOH is 1:(1-6).

4. The method for preparing an activated carbon carrier for low-temperature NH3-SCR denitrification according to claim 2, characterized in that: During the activation reaction, the mixed material is heated from room temperature to 600-900° C. at 5° C. / min under the protection of an inert atmosphere, and kept warm for 1-2 hours.

5. The method for preparing an activated carbon carrier for low-temperature NH3-SCR denitrification according to claim 2, characterized in that: The particle size of the activated carbon particles is 20-60 meshes, and the particle size of the activated carbon carrier is 40-60 meshes.

6. A KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitration, characterized in that: The general formula of the KOH-modified activated carbon-supported copper catalyst is: AC-xK-yCu; Wherein, AC is coal-based activated carbon, K is activator KOH, x is the mass ratio of KOH to AC, x is 1-6, and y is the loading amount of Cu, y is 1wt%-15wt%.

7. The method for preparing a KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitration according to claim 6, characterized in that: The activated carbon carrier for low-temperature NH3-SCR denitrification according to claim 1 comprises the following steps: The activated carbon carrier is impregnated with an equal volume of a copper salt solution for reaction, and then dried to obtain a KOH-modified activated carbon-supported copper catalyst.

8. The method for preparing a KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitration according to claim 7, characterized in that: The copper salt solution includes a mixture of Cu(NO3)2·3H2O and deionized water; in the KOH-modified activated carbon-supported copper catalyst, the loading amount of Cu is 1wt%-15wt%.

9. An application of the KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitration according to claim 6, characterized in that: The KOH-modified activated carbon-supported copper catalyst is used for denitration reaction to remove NO in coke oven flue gas. X .

10. The use of KOH-modified activated carbon-supported copper catalyst for low-temperature NH3-SCR denitration according to claim 9, characterized in that: The denitration reaction specifically includes the following steps: placing the KOH-modified activated carbon-loaded copper catalyst in a quartz tube, filling both ends of the quartz tube with quartz sand and quartz wool, and then placing the quartz tube in a reaction device, and introducing a mixed gas of NH3, NO, O2 and N2; wherein the total flow rate of the mixed gas is 100ml / min-300ml / min, and the reaction temperature is 100℃-220℃.

Citation Information

Patent Citations

  • Catalyst for desorbing nitrogen oxides and carbon monoxide at low temperature and preparation method thereof

    CN103406122A

  • Two-step activation preparation method of activated carbon and application thereof in supercapacitor

    CN106145110A

  • Preparation method of lignite-based activated carbon with high specific surface area

    CN113233462A

  • Preparation method of nano copper oxide and application thereof

    CN113247942A

  • Preparation method of high specific surface area coal mass active carbon

    CN1948147A